The four faces of information visualization: A conceptual framework for a postgraduate program - Botelho, M. C.; Vilar, E. T.; Cardoso, E.; Silva, A. A.; Almeida, P. D.; Rodrigues, L. M.; Martinho, A. P.; Rodrigues, S. (2017 12th Iberian Conference on Information Systems and Technologies (CISTI), 2017)
The multidisciplinary nature of information visualization is today fairly consensual in both professional and academic communities: data analysis, information design, storytelling, among other subjects, are common drivers in this field. The systematic study of this cross-fertilization, patent in the way the concept's definition varies according to the perspective being adopted, represents an important and needed addition to the critical mass of a relatively recent area of knowledge. The proposal of a single unified definition of information visualisation being beyond the scope of this paper, it instead summons and discusses its multiple viewpoints to help designing a postgraduate program on the topic, aiming to simultaneously start an open debate as its implementation phase goes on and new questions are subsequently raised.